Trends in stratospheric and free tropospheric ozone - Harris, N. R. P.; Ancellet, G.; Bishop, L.; Hofmann, D. J.; Kerr, B.; McPeters, R. D.; Préndez Bolívar, Margarita; Randel, W. J.; Staehelin, J.; Subbaraya, B. H.; Volz-Thomas, A.; Zawodny, J.; et al. (AMER GEOPHYSICAL UNION, 1997)
Artículo de publicación ISI Current understanding of the long-term ozone trends is described. Of particular concern is an assessment of the quality of the available measurements, both ground and satellite based. Trends in total ozone have been calculated for the ground-based network and the combined data set from the solar backscatter ultraviolet (SBUV) instruments on Nimbus 7 and NOAA 11, At midlatitudes in the northern hemisphere the trends from 1979 to 1994 are significantly negative in all seasons and are larger in winter/spring (up to 7%/decade) than in summer/fall (about 3%/decade). Trends in the southern midlatitudes are also significantly negative in all seasons (3 to 6%/decade), but there is a smaller seasonal variation, In the tropics, trends are slightly-negative and at the edge of being significant at the 95% confidence level: these tropical trends are sensitive to the low ozone amounts observed near the end of the record and allowance must also be made for the suspected drift in the satellite calibration. The bulk of the midlatitude loss in the ozone column has taken place at altitudes between 15 and 25 km. There is disagreement on the magnitude of the reduction, with the SAGE I/II record showing trends as large as -20 +/- 8%/decade at 16-17 km and the ozonesondes indicating an average trend of -7 +/- 3%/decade in the northern hemisphere. (All uncertainties given in this paper are two standard errors or 95% confidence limits unless stated otherwise), Recent ozone measurements are described for both Antarctica and the rest of the globe, The sulphate aerosol resulting from the eruption of Mount Pinatubo in 1991 and dynamic phenomena seem to have affected ozone levels, particularly at northern midlatitudes and in the Antarctic vortex, However, the record low values observed were partly caused by the long-term trends and the effect on the calculated trends was less than 1.5%/decade.